Effect of Tonifying deficiency and Zhengqi porridge on immune function reconstruction in HIV/AIDS patients with Qi deficiency (补虚正气粥对艾滋病气虚型患者免疫功能重建的影响研究) - WEI Yan (魏艳); LI shu (李树); YUAN Hongxia (袁洪霞); ZHANG Ying (张英); LIU Xiaoli (刘小丽); LIU Lingling (刘玲玲) (中西医结合护理)
Objective To observe the effect of Tonifying deficiency and Zhengqi porridge on immune function reconstruction of HIV/AIDS patients with Qi deficiency. Methods Sixty (Human Immunodeficiency Virus/ Acquired Immunodeficiency Syndrome)HIV/AIDS patients admitted to the center for Disease Control and prevention in Huichuan District of Zunyi City were randomly divided into control group and treatment group by random number table. All patients received the highly active anti-retroviral therapy, and those in the treatment group were given Tonifying deficiency and Zhengqi porridge. The CD4+ T-cell count was measured before, 3 months and 6 months after intervention. The Effective reconstitution of immune function was analyzed. Results After 3 and 6 months of treatment, the immune reconstitution in the treatment group was better than that in the control group for patients with CD4+ T-cell count of 100-500/mm3 (P＜0. 05). Conclusion Tonifying deficiency and Zhengqi porridge can promote the reconstruction of immune function in HIV / AIDS patients with Qi deficiency and help to restore immune function. (目的 探讨补虚正气粥对人类免疫缺陷病毒(HIV)感染及艾滋病(AIDS)气虚型患者的免疫功能恢复作用。方法 选择遵义市汇川区疾病预防控制中心60名HIV/AIDS患者, 随机将患者分为治疗组和对照组, 各30例。对照组按传统方法进行HAART(高效抗反转录病毒)治疗, 治疗组则在对照组治疗的基础上加用补虚正气粥。于干预前、干预后3个月和干预后6个月比较两组患者CD4+T淋巴细胞计数值和免疫功能重建有效率。结果 对于干预前CD4+T淋巴细胞计数100～500个/mm3的患者, 在介入3个月和6个月, 治疗组免疫功能的恢复较对照组好(P＜0. 05)。结论 补虚正气粥对HIV/AIDS气虚型患者免疫功能重建有促进作用, 有助于免疫功能的重建。)